Reimagining UKCS transfers: improving the effectiveness of the Master Deed and the UKCS transfer regime. (27th February 2016) - Anthony, David
Abstract : When the Master Deed was conceived one of its core objectives was to expedite and simplify the United Kingdom Continental Shelf (UKCS) asset transfer regime. Although the Master Deed has had some successes since its introduction in 2003, its effectiveness in reducing the time and cost of asset transfers in the UKCS has been hindered by an inconsistent application of legal principles and the overtly adversarial legal and commercial culture that prevails in the UKCS. The UKCS's viability to continue as a profitable producing basin is currently under threat as margins are squeezed by high producing costs and low commodity prices. During such times of increased financial pressure, it is imperative that regulators react to these challenges by developing and nurturing a regulatory environment that reduces administrative obstacles associated with asset transfers encouraging greater liquidity and investment. This article argues that with the support of a proactive and collaborative regulator, which safeguards the consistent application of transfer provisions, discards outdated methodologies and fosters a more collaborative culture between UKCS participants, the UKCS transfer regime has the potential to be one of the most dynamic and user friendly regimes of its kind. Maximizing the effectiveness of the transfer regime will ensure that the UKCS remains a competitive environment to carry out oil and gas operations, elongating its producing life and increasing overall hydrocarbon recovery.